The (totally not) guaranteed guide to friends, foes & faux friends - McCafferty, Megan (McCafferty, Megan., 2015)
New seventh-grader Jessica Darling decides to host a huge slumber party in order to unite her grade school friends with her new middle school friends, and maybe even get popular.